IMPACT OF COASTAL ENGINEERING SOLUTIONS ON WATER EXCHANGE AND SEDIMENT TRANSPORT IN NAI LAGOON (NINH THUAN) - Vinh, Vu Duy (Vietnam Journal of Marine Science and Technology, 2018)
With the area of only about 700 ha, Nai lagoon has a great contribution to ecology as well as socioeconomic development of Ninh Hai disctrict and Phan Rang-Thap Cham city (Ninh Thuan province). However, the deposition tendency has occurred recently, making the lagoon shallower. It also causes the decrease in water exchange as well as environmental degradation in this area. Therefore, solutions that increase water exchange and reduce the deposition rate in the Nai lagoon are necessary. Based on the Delft3D model with MORFAC approach, this paper gives some assessments on the impact of coastal engineering solution on water exchange and sediment transport. The simulation scenarios include as extending present jetties to 165 m long, extending present jetties combined with dredging lagoon inlet, extending only northeast jetty to 260 m long combined with dredging lagoon inlet, and dredging all lagoon area. The results show that the change in water exchange is very small (almost below 1%), except in the case of dredging the entire lagoon area, water exchange decreases about 10% (due to the increase of the lagoon water volume) compared with the present. Sediment flux balance at cross-section MCI (Tri Thuy bridge) also changes slightly under influence of coastal engineering works. On the other hand, sediment flux from the coastal zone into the inlet (cross-section 2- MCII) and alongshore to Southwest (cross-section MCIII) have strongly decreased. Especially, in the scenario of extending northeast jetty combined with and dredging the inlet zone, net sediment flux into the inlet decreases from 637 m3/day to 180 m3/day (droughty year) and from 535 m3/day to 80 m3/day in the flood year.